Efficacy and Tolerability of Miltefosine in the Treatment of Cutaneous Leishmaniasis. (28th October 2020) - Ware, JeanAnne M; O'Connell, Elise M; Brown, Thomas; Wetzler, Lauren; Talaat, Kawsar R; Nutman, Thomas B; Nash, Theodore E
Abstract: Background: Cutaneous leishmaniasis (CL) is a neglected tropical disease causing an estimated 1 million new cases annually. While antimonial compounds are the standard of care worldwide, they are associated with significant adverse effects. Miltefosine, an oral medication, is United States (US) Food and Drug Administration approved to treat CL caused by Leishmania braziliensis, Leishmania guyanensis, and Leishmania panamensis. Evidence of efficacy in other species and side-effect profiles in CL has been limited. Methods: Twenty-six patients with CL were treated with miltefosine at the US National Institutes of Health. Species included L. braziliensis (n = 7), L. panamensis (n = 5), Leishmania mexicana (n = 1), Leishmania infantum (n = 3), Leishmania aethiopica (n = 4), Leishmania tropica (n = 2), Leishmania major (n = 1), and unspeciated (n = 3). Demographic and clinic characteristics of the participants, response to treatment, and associated adverse events were analyzed. Results: Treatment with miltefosine resulted in cure in 77 % (20/26) of cases, with cures among all species. Common adverse events included nausea/vomiting (97%) and lack of appetite (54%). Clinical management or dose reduction was required in a third of cases. Gout occurred in 3 individuals with a prior history of gout. Most laboratory abnormalities, including elevated creatinine and aminotransferases, were mild and normalized after treatment. Conclusions: Our data suggest that miltefosine has good but imperfect efficacy to a wide variety of Leishmania species. While side effects were common and mostly mild to moderate, some resulted in discontinuation of therapy. Due to oral administration, broad efficacy, and manageable toxicities, miltefosine is a viable alternative treatment option for CL, though cost and lack of local availability may limit its widespread use. Abstract : Miltefosine is an oral therapy for cutaneous leishmaniasis with advantages of ease of administration and efficacy for most species based on limited studies. Mild-to-moderate adverse events were common and reversible but led to early discontinuation in some patients.